The Use of Crisis Communication Strategies by Erigo in Emergency Management and Plagiarism Issues - Kinkin Yuliaty Subarsa Putri; Luthfi Fazli; Helyana Wulandari; Nada Arina Romli; Wiratri Anindhita (Jurnal the Messenger, 2024)
Introduction: Erigo serves as a compelling research subject due to its recent reputation crisis from plagiarism allegations, illustrating how companies can face significant brand challenges. Its application of Image Repair Theory offers insights into effective crisis communication strategies, while the role of social media highlights the dynamics of public perception. Analyzing Erigo’s experience provides valuable lessons for other brands facing similar ethical issues.